2023
DOI: 10.1021/acsomega.2c07227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short Glass Fiber Addition on Flexural and Impact Behavior of 3D Printed Polymer Composites

Abstract: Fused deposition modeling (FDM), one of the most widely used additive manufacturing (AM) processes, is used for fabrication of 3D models from computer-aided design data using various materials for a wide scope of applications. The principle of FDM or, in general, AM plays an important role in minimizing the ill effects of manufacturing on the environment. Among the various available reinforcements, short glass fiber (SGF), one of the strong reinforcement materials available, is used as a reinforcement in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
(59 reference statements)
0
16
1
Order By: Relevance
“…In terms of competitive results or superiorities, it can be noted that the flexural properties of GF/ABS composites reported in the present work (64.46 and 3549.71 MPa) were higher than the maximum flexural properties reported in Reference [38] for CF/ABS composites at any nozzle temperature. This suggested that the GF/ABS composites might provide competitive results or superiorities in terms of flexural properties compared with CF/ABS composites processed under similar conditions.…”
Section: Resultscontrasting
confidence: 62%
“…In terms of competitive results or superiorities, it can be noted that the flexural properties of GF/ABS composites reported in the present work (64.46 and 3549.71 MPa) were higher than the maximum flexural properties reported in Reference [38] for CF/ABS composites at any nozzle temperature. This suggested that the GF/ABS composites might provide competitive results or superiorities in terms of flexural properties compared with CF/ABS composites processed under similar conditions.…”
Section: Resultscontrasting
confidence: 62%
“…The effective Schiff base condensation reaction with the formation of ligands was supported by the disappearance of the υ(-NH 2 ) stretching vibration of ophenylenediamine (3383-3364 cm À1 ) and υ(C=O) of salicylaldehyde (1725 cm À1 ) and the appearance of new peak at 1660-1677 cm À1 owing to υ(C=N) azomethine group. This band was further shifted to the lower frequency (1548-1654 cm À1 ) in the case of the metal(II) complexes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), which indicates the involvement of azomethine nitrogen in coordination with the metal ions. 23 The ligands (HL [1][2][3][4] ) showed a broad band at 3379-3390 cm À1 due to the phenolic υ(O-H) stretching, which was absent in the spectra of complexes, indicating the deprotonation of phenolic (O-H) group and formation of a bond between phenolic-oxygen and metal ion.…”
Section: Ft Ir Spectral Studiesmentioning
confidence: 93%
“…Thus, FMOs provide significant information to understand drug metabolism and a large number of drugs are metabolized by oxidation and reduction reactions. The orbital energy diagram for ligands (HL 1À4 ) and complexes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) are shown in Figures 3 and S14 The biological activity of the molecules may be influenced by the smaller energy gap value and easy charge transfer in the complexes. The complexes 2, 6, and 10 exhibit high biological activity due to the presence of an electron-donating methoxy group that might be entered into the conjugation, leading to a small energy gap and easy intramolecular charge transfer (ICT).…”
Section: Frontier Molecular Orbitals (Fmos) Analysismentioning
confidence: 99%
See 2 more Smart Citations